The concept of consciousness in psycholinguistics via inductive and deductive methods - Nasyhovna, Maklakova Evgeniya Mikhaylovna, Farrakhova Gulnaz Faizovna, Slavina Liliya Rustamovna, Mustafina Jamila (Opción, 2019)
This review article is devoted to the concept of consciousness in psycholinguistics via inductive and deductive methods, the classification of modeling of different levels of understanding and systems. As a result, the term consciousness is considered to be reflexive psychological activity, including perceptions, processing perceived and forming an integral picture of the world, containing knowledge and relations, objects and the subject itself in relation to them. As a conclusion, in the scientific community consciousness is considered to be the highest function of the brain that is unique to human and connected with speech.